THU0541 Association Between Periodontitis and the Risk of Etanercept withdrawal in Anti-TNF-Naïve Rheumatoid Arthritis Patients: A Nationwide Population-Based Cohort Study. (23rd January 2014) - Chen, H.-H.; Chen, D.-Y.; Huang, N.; Lai, K.-L.; Chen, Y.-M.; Chou, Y.-J.; Chou, P.; Lin, C.-H.
Abstract : Background: Given the epidemiologic and immunologic findings, it is hypothesized that that PD may be a risk factor not only for the initiation but also for the progression of RA. To date, only a small study has shown that PD may also influence the anti-TNF treatment response in patients with RA. Objectives: To investigate the association between periodontitis (PD) and etanercept survival in anti-tumor necrosis factor (anti-TNF)-naïve patients with rheumatoid arthritis (RA). Methods: This retrospective nationwide population-based cohort study identified 3359 anti-TNF-naïve RA patients (age at diagnosis ≥ 16 years) in whom etanercept (ETN) treatment was initiated using administrative data. Two variables regarding PD exposure were used for analysis: PD during the 5 years before ETN administration (history of PD) and PD between ETN start date and stop date (concurrent PD). The association between PD and ETN withdrawal was quantified by calculating hazard ratios (HRs) with 95% confidence intervals (CIs) using Cox proportional hazard regression analysis, after adjustment for potential confounders. Results: An interaction between concurrent PD and the drug survival time was demonstrated. To avoid violating the assumption for the Cox proportional regression model, analysis was stratified by concurrent PD. A history of PD was associated with increased risk of ETN withdrawal in patients with concurrent PD (HR, 1.27; 95% CI, 1.01–1.60) and those without concurrent PD (HR, 1.17; 95% CI, 1.06–1.30). This association was stronger in the concurrent PD group with more PD-related visits (≥5) during the 5 years before ETN administration (RR, 1.62; 95% CI, 1.23–2.14). Concomitant methotrexate or leflunomide administration had a protective effect on etanercept withdrawal in patients without concurrent PD, but the effect was attenuated in patients with concurrent PD. Conclusions: A history of PD before ETN administration was associated with an increased risk of ETN withdrawal in anti-TNF-naïve RA patients. References: Marotte H, Farge P, Gaudin P, et al. The association between periodontal disease and joint destruction in rheumatoid arthritis extends the link between the HLA-DR shared epitope and severity of bone destruction. Ann Rheum Dis 2006;65 :905-9. Ribeiro J, Leao A, Novaes AB. Periodontal infection as a possible severity factor for rheumatoid arthritis. J Clin Periodontol 2005;32 :412-6. Ortiz P, Bissada NF, Palomo L, et al. Periodontal therapy reduces the severity of active rheumatoid arthritis in patients treated with or without tumor necrosis factor inhibitors. J Periodontol 2009;80 :535-40. Savioli C, Ribeiro AC, Fabri GM, et al. Persistent periodontal disease hampers anti-tumor necrosis factor treatment response in rheumatoid arthritis. J Clin Rheumatol 2012;18 :180-4. Acknowledgements: We thank the members of the Bureau of National Health Insurance, Department of Health, and the National Health Research Institutes for providing and managing, respectively, the National Health Insurance Research Database. This study was supported by grant TCVGH-1023805C from Taichung Veterans General Hospital, Taiwan. Disclosure of Interest: None Declared